Clinical outcome and health-related quality-of-life following microsurgical reconstruction in patients with oral and oropharyngeal cancer. (4th May 2017) - Al-Hayder, Shems; Elberg, Jens Jørgen; Charabi, Birgitte
Abstract: Conclusion: Radial forearm free flap (RFFF) and fibula free flap (FFF) provide high safety and reliability with low incidence of free flap failure and an acceptable level of complications and health-related quality-of-life (HRQoL). Objectives: To determine the clinical outcomes and long-term HRQoL in patients with oral or oropharyngeal cancer following free flap reconstruction. Methods: A retrospective review of medical records and self-administered HRQoL questionnaires, EORTC QLQ-C30, and -H&N35. All patients who underwent surgery for oral or oropharyngeal cancer followed by primary reconstruction by RFFF or FFF at Rigshospitalet between September 2001 and November 2011 were included. Results: The study comprised 19 patients still alive out of 61 patients. The free flap success rate was 94.7%. Early post-operative complications occurred in 11 patients (57.9%); however, only three cases (15.8%) required re-surgery. Nine patients (47.4%) developed late complications, including mandibular osteoradionecrosis in six cases (31.6%). Most patients obtained acceptable values of global quality-of-life and relatively high scores on the functional scales.